#Donate: the role of social media in academic library fundraising. Issue 2 (8th August 2016) - Garczynski, Joyce
Abstract : Purpose: The purpose of this study is to examine the extent to which academic libraries are using social media to fundraise, what tactics they are using to fundraise on social media and how academic libraries' social networks are responding to their fund-raising efforts. Design/methodology/approach: This research is a content analysis of 276 posts from 2015 on the Facebook, Twitter and Instagram accounts of 16 academic libraries. Findings: This study found that academic libraries are just beginning to use social media for fund-raising with many adopting non-profit best practices that brought significantly more likes and shares/retweets to their accounts. Originality/value: This research is one of the few systematic examinations of how libraries use social media to discuss fund-raising, and the findings suggest tactics for libraries to adopt in their fund-raising posts to generate more likes and shares/retweets.